The So Ethnic Group: Ways of Living, Sociocultural Characteristics and Changes - Surifai, Theparak; Bangperng , Kiattsak; Meethaisong, Theerapong (Dhammathas Academic Journal, 2023)
This research aimed to examine the so ethnic group's ways of living and sociocultural characteristics. It also investigated the social and cultural changes in the Isan society context. This qualitative research design focused on the process of fieldwork collected from the so ethnic group through observation, survey, and interviews. There were 74 key informants via purposive sampling. The data were analyzed via content analysis following the research objectives. The findings showed that: 1. The So ethnic group belongs to the Austroasiatic language family, Mon-Khmer branch, or Katuic. Historically, the so ethnic group moved from Laos in the early Rattanakosin Period. In their traditional society, the so held ‘Heet Kong’ or a belief in ghosts in different ways. Such beliefs became behavioural models and relationships among people in the group. They had a unique way of life, language, beliefs, cultures and traditions where they became like an ethnic border from other ethnic groups, especially Lao/Isan people. They are often perceived as inferior to other ethnic groups by outsiders. 2. Currently, the so ethnic group is under the Thai state, they have integrated into the Thai nation through technology power, such as education, religion and bureaucracy. These cause social and cultural changes in various aspects, including modifying lifestyles and society following other people in the Isan community. Such practices of the ‘Heet Kong’ have been modified in order to conform with the local people in the Isan society.